Kelembagaan Dana Bergulir Upk Pasca Berakhirnya PNPM-MPd di Upk Candipuro Kabupaten Lumajang - Hadi Sulistyo; V Rudi Handoko (Journal of Innovation and Applied Technology, 2019)
This study aims to describe how the revolving fund institutional activities at UPK PNPM-MPd post program and to find out what are the obstacles and problems that arise in institutional management. This research is a qualitative descriptive study. Researcher data collection uses several methods including: documentation, observation and interviews with actors and beneficiaries of revolving fund activities, including: administrators of BKAD, UPK, BP-UPK, Verification Team and Funding Team. The study was conducted at the Ex-PNPM-MPd UPK in Candipuro District, Lumajang Regency.